The epistemic injustice Framework in Sociological Studies of religion - Hall, Dorota (Studia Socjologiczne, 2025)
The article tests the applicability of the epistemic injustice framework in sociological research on religion. In the first step, it introduces the concept of epistemic injustice as presented by Fricker (2007) and subsequent refinements of this concept, in particular those inspired by gender studies and critical race studies. In the second step, the article shows how the issue of epistemic injustice has already been taken into account in academic reflection on religion. In the third step, it explains why using the framework of epistemic injustice is particularly promising for sociological studies of religion, suggests research topics that could outline the ‘epistemic geography’ of religion in Poland, and details potential research questions.